The effects of ionizing radiation on the structure and antioxidative and metal-binding capacity of the cell wall of microalga Chlorella sorokiniana. (December 2020) - Vojvodić, Snežana; Luković, Jelena Danilović; Zechmann, Bernd; Jevtović, Mima; Pristov, Jelena Bogdanović; Stanić, Marina; Lizzul, Alessandro Marco; Pittman, Jon K.; Spasojević, Ivan
Abstract: The impact of ionizing radiation on microorganisms such as microalgae is a topic of increasing importance for understanding the dynamics of aquatic ecosystems in response to environmental radiation, and for the development of efficient approaches for bioremediation of mining and nuclear power plants wastewaters. Currently, nothing is known about the effects of ionizing radiation on the microalgal cell wall, which represents the first line of defence against chemical and physical environmental stresses. Using various microscopy, spectroscopy and biochemical techniques we show that the unicellular alga Chlorella sorokiniana elicits a fast response to ionizing radiation. Within one day after irradiation with doses of 1–5 Gy, the fibrilar layer of the cell wall became thicker, the fraction of uronic acids was higher, and the capacity to remove the main reactive product of water radiolysis increased. In addition, the isolated cell wall fraction showed significant binding capacity for Cu 2+, Mn 2+, and Cr 3+ . The irradiation further increased the binding capacity for Cu 2+, which appears to be mainly bound to glucosamine moieties within a chitosan-like polymer in the outer rigid layer of the wall. These results imply that the cell wall represents a dynamic structure that is involved in the protective response of microalgae to ionizing radiation. It appears that microalgae may exhibit a significant control of metal mobility in aquatic ecosystems via biosorption by the cell wall matrix. Graphical abstract: Image 1 Highlights: Ionizing radiation represents an environmental factor of increasing importance. Microalga Chlorella sorokiniana elicits a fast response to ionizing radiation. The fibrilar layer of the cell wall becomes thicker. Antioxidative and metal-binding capacities of the cell wall increase. Cell wall is involved in the protective response of microalgae to radiation.